اليات تحكيم المقلات العلمية الضوابط والمعايير - برني, لطيفة; ‫فالتة‬, ‫اليمين‬ (مجلة الاقتصاديات المالية البنكية وإدارة الأعمال, 2018)
This article aims to display the role of peer review in Scientific Quality Control of research and give the review it’s Personal Character. Because that, this article looking for mechanisms and requirements that achieve objectivity and transparency in research peer review, and that is through the different Controls and standards, how to choose reviewers, and the preparation of the report. Also the article benefited from national and international peer review model, and put a model to control and improve this operation .Included, it see to response to this question: what is the objectives of peer review? What is it’s importance? What is it’s standards and mechanisms? How to choose the reviewers? What after the peer review process? What adjusts the writing of the reviewers report? What is the impact factor? Finally, how scientific reviews acquire their legal value?